2012
DOI: 10.1007/978-3-642-24707-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Breakup Reaction Models for Two- and Three-Cluster Projectiles

Abstract: Breakup reactions are one of the main tools for the study of exotic nuclei, and in particular of their continuum. In order to get valuable information from measurements, a precise reaction model coupled to a fair description of the projectile is needed. We assume that the projectile initially possesses a cluster structure, which is revealed by the dissociation process. This structure is described by a few-body Hamiltonian involving effective forces between the clusters. Within this assumption, we review variou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(110 citation statements)
references
References 138 publications
(364 reference statements)
3
107
0
Order By: Relevance
“…(11) and in the S-matrices [Eqs. (14)- (18)] are used for calculations of the cross sections [Eqs. (19)- (24)] in the cases of scattering and breakup of 11 Be on protons and nuclei that will be considered in the following part of our work.…”
Section: B Momentum Distributions Of Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) and in the S-matrices [Eqs. (14)- (18)] are used for calculations of the cross sections [Eqs. (19)- (24)] in the cases of scattering and breakup of 11 Be on protons and nuclei that will be considered in the following part of our work.…”
Section: B Momentum Distributions Of Fragmentsmentioning
confidence: 99%
“…[13], not only scattering but also the breakup of 11 Be in the collisions with the target nuclei 93 Nb, 181 Ta, and 238 U play a decisive role when studying the internal cluster structure of 11 Be. Indeed, the narrow peak of the momentum distributions of the breakup fragments of such a neutron-rich nucleus reflects the very large extension of its wave function, compared to that of the core nucleus 10 Be, and thus evidences the existence of the nuclear halo [14][15][16][17][18][19][20]. As was concluded in [18], namely the longitudinal component of the momentum (taken along the beam or the z-direction) provides the most accurate information on the intrinsic properties of the halo, being insensitive to details of the collision and the size of the target.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the momentum distribution of the breakup fragments has a narrow peak, much narrower than that observed in the fragmentation of well bound nuclei. This property has been interpreted (e.g., [13][14][15][16][17][18][19]) to be related to the very large extension of the wave function, as compared to that of the core nucleus, leading to the existence of the nuclear halo. As pointed out in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Only the full ground state wave function of the projectile, of any orbital angular momentum configuration, enters in this theory as input. Thus, unlike most of the theoretical models described in a recent review of breakup theories [32], this approach does not require the knowledge of the positions and widths of the continuum states. Hence, it is free from the uncertainties associated with the multipole strength distributions [33] that may exist in some of these theories.…”
Section: The Coulomb Dissociation Modelmentioning
confidence: 99%